EVALUASI PELAKSANAAN PELATIHAN JARAK JAUH TEKNOLOGI INFORMASI DAN KOMUNIKASI TINGKAT MADRASAH TSANAWIYAH ANGKATAN 2 (GURU MATEMATIKA) TAHUN 2022 - Muhammad Ridwan (Balai Diklat Keagamaan Medan, 2022)
This research entitled is the Evaluation of the Implementation of Information and Communication Technology Distance Training for Madrasah Tsanawiyah Class 2 (Mathematics Teachers). The purpase of this study is to evaluate the implementation of the distance training seen from the documents in the Medan Religious Education and Training Center Learning Management System (LMS). From the results of the document research and data processing taken from the Bdk Medan LMS, it's found that the participants’ attitude assessment given by the committee was with an average value of 83.25 with “good” qualifications, for knowledge assessment with an average value of 79.45 with “competent” qualifications and the skills provided by widyaiswara are with an average value of 80.73 with